2022
DOI: 10.1002/ctm2.1022
|View full text |Cite
|
Sign up to set email alerts
|

The potential of gas plasma technology for targeting breast cancer

Abstract: Despite therapeutic improvements in recent years, breast cancer remains an often fatal disease. In addition, breast cancer ulceration may occur during late stages, further complicating therapeutic or palliative interventions. In the past decade, a novel technology received significant attention in the medical field: gas plasma. This topical treatment relies on the partial ionization of gases that simultaneously produce a plethora of reactive oxygen and nitrogen species (ROS/RNS). Such local ROS/RNS overload in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 267 publications
0
7
0
Order By: Relevance
“…The first application is the direct and topical treatment of superficial tumors. In terms of potential targets for gas plasma treatment in patient-derived samples, this includes skin cancer, such as melanoma [217] and cutaneous squamous cell and basal cell carcinoma [218], as well as ulcerating cancers breaking through the skin, such as breast cancer [219][220][221] and oral and head and neck squamous cell carcinoma [161,222,223] and oral precancerous lesions [224]. In addition, for most of these tumor types, in vivo studies had shown pro-immunogenic effects of plasma treatment as indicated above.…”
Section: Clinic-related Concepts For Plasma Supporting Anticancer Imm...mentioning
confidence: 99%
“…The first application is the direct and topical treatment of superficial tumors. In terms of potential targets for gas plasma treatment in patient-derived samples, this includes skin cancer, such as melanoma [217] and cutaneous squamous cell and basal cell carcinoma [218], as well as ulcerating cancers breaking through the skin, such as breast cancer [219][220][221] and oral and head and neck squamous cell carcinoma [161,222,223] and oral precancerous lesions [224]. In addition, for most of these tumor types, in vivo studies had shown pro-immunogenic effects of plasma treatment as indicated above.…”
Section: Clinic-related Concepts For Plasma Supporting Anticancer Imm...mentioning
confidence: 99%
“…Breast cancer (BC), the most prevalent malignant tumor globally, is characterized by significant heterogeneity 1 . It poses a considerable health risk to women 2–4 .…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer (BC), the most prevalent malignant tumor globally, is characterized by significant heterogeneity. 1 It poses a considerable health risk to women. [2][3][4] Despite advances in early detection and treatment, drug resistance remains a primary obstacle, often leading to poor prognosis in various malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Many genetic, environmental, and lifestyle factors have a role in the onset and spread of BRCA [ 1 ]. Much research has been done over the years to identify the underlying causes of BRCA and to create efficient treatment plans [ [ 2 , 3 ]].…”
Section: Introductionmentioning
confidence: 99%